Peranan Senam Aerobik dalam Mengendalikan Tekanan Darah pada Penderit Hipertensi - Grido Handoko Sriyono; Nur Hamim; Umi Narsih (Jurnal Health Sains, 2023)
One of the good physical activities to improve physical fitness is aerobic exercise. Someone who does not have the habit of aerobic exercise 30-50% tendency to develop hypertension. Regular aerobic exercise can lower blood pressure effectively. Physical activity with aerobic exercise is recommended for 30 minutes per day and 3 days per week. To determine the correlation between aerobic exercise habits and blood pressure in patients with hypertension in Karangperanti Village. The design of this research is descriptive correlative with a cross sectional approach. The population is 120 respondents with a sample of 60 respondents, using purposive sampling technique and data collection using non-standard questionnaires. Using bivariate data analysis Pearson Correlation. The study showed that the habit of aerobic exercise with blood pressure of patients with hypertension in Karangperanti Village with 60 respondents found that regular aerobic exercise activities were 32 respondents (52.8%). Irregular activity there are 28 respondents (47.2%). The frequency based on the respondent's blood pressure showed that the TDS had a median value of 150 mmHg, a minimum value of 140 mmHg and a maximum value of 185 mmHg with an average value of 152.55 mmHg and a standard deviation of 11.814 mmHg. Meanwhile, TDD has a median value of 92 mmHg, a minimum value of 90 mmHg and a maximum value of 120 mmHg with an average value of 95.11 mmHg and a standard deviation of 5.155 mmHg. There is a correlation between aerobic exercise habits and blood pressure in patients with hypertension in Karangperanti Village, p value 0.000 (α = 0.05). It is expected that people with hypertension always do aerobic exercise habits that are carried out for one week at least 3 times with a duration of 30 minutes.